PEMANFAATAN SENSOR COASTAL ZONE COLOR SCANNER (CZCS) DAN OCEAN COLOR AND TEMPERATURE SCANNER (OCTS) DALAM IDENTIFIKASI KESUBURAN PERAIRAN DAN DAERAH PENANGKAPAN IKAN - Sachoemar, Suhendar I (Jurnal Hidrosfir Indonesia, 2006)
The spatial distribution of the water productivity bio-optically can be identifiedand detected by using visible infrared sensor of Coastal Zone Color Scanner(CZCS) carried by the satellite Nimbus 7. Since the availability of the ADEOS(Advance Earth Observation Satellite) that carried both sensors of the visiblenear infrared and near infra red on the OCTS (Ocean Color andTemperature Scanner) in August 1996, beside the water productivity,the fishing ground also is hoped can be studied all at once by using twoidentification methods of the SST ( Sea Surface Temperature) and OceanColor.